Pelvic organ prolapse and uterine preservation: a survey of female gynecologists (POP-UP survey) - Peter Urdzík; Vladimir Kalis; Mija Blaganje; Zdenek Rusavy; Martin Smazinka; Martin Havir; Rastislav Dudič; Khaled M. Ismail (BMC, 2020)
Abstract Background The aim of this study was to explore the personal views of female gynecologists regarding the management of POP with a particular focus on the issue of uterine sparing surgery. Methods A questionnaire based survey of practicing female gynecologists in the Czech Republic, Slovenia and Slovakia. Results A total of 140 female gynecologists from 81 units responded to our questionnaire. The majority of respondents stated they would rely on a urogynecologist to aid them with their choice of POP management options. The most preferred options for POP management were sacrocolpopexy and physiotherapy. Almost 2/3 of respondents opted for a hysterectomy together with POP surgery, if they were menopausal, even if the anatomical outcome was similar to uterine sparing POP surgery. Moreover, 81.4% of respondents, who initially opted for a uterine sparing procedure, changed their mind if the anatomical success of POP surgery with concomitant hysterectomy was superior. Discussing uterine cancer risk in relation to other organs had a less significant impact on their choices. Conclusions The majority of female gynecologists in our study opted for hysterectomy if they were postmenopausal at the time of POP surgery. However, variation in information provision had an impact on their choice.